Character Education in an Acehnese Cultural Saga: Hikayat Prang Sabi - RN Herman; Mukhlis Mukhlis; Firman Parlindungan; Lia Lisyati; Rahmad Nuthihar (Lingua Cultura, 2020)
The research sought to understand the value of patriotism in the Hikayat Prang Sabi by using a qualitative approach. Hikayat was referred to narratives (saga) of war rooted in Acehnese cultural tradition, and Prang Sabi in Acehnese language meant ‘Holy War’. As a literary work, Hikayat Prang Sabi embodied the concept of jihad, which was usually sung during the time of war in the Acehnese history: Portuguese in 1511, Dutch in 1873, Japan in 1942, and the Republic of Indonesia in 1976. The source of the data was verses or stanzas of Hikayat Prang Sabi that contained patriotic values. These verses were then treated as the unit of analysis. A hermeneutic approach was employed to analyze the data. The findings show that Hikayat Prang Sabi contains two types of patriotic values: national and religious. National value refers to the sense of nationalism, ethnicity, and humanity. Religious value, on the other hand, displays the value of spirituality, prophecy, and peace. These values indicate the foundation of thinking and doing of the Acehnese people manifested in a literary work, which then can be transferred into the notion of character education.